Enhenced gas sensing perfomance induced by CuO-ZnO heterostructure towards NO2 gas - Maebana, Lekgolo Malesela (My University, 2023)
The selective detection of gaseous benzene, toluene, ethylbenzene, and xylene (BTEX) is challenging due to their similar molecular structures. In addition, BTEX vapours are extremely hazardous and carcinogenic. Thus, in the current study, n-type ZnO and p-type CuO nanostructures were synthesized utilizing various bases by a simple hydrothermal method. Among the tested sensors, the ZnO-NaOH-based sensor displayed a temperature dual-mode selectivity toward benzene with responses (Ra/Rg) of 2.5 and 24 at 5 and 100 ppm, respectively at 75 C, and Ra/Rg  142 toward xylene vapour at 100 ppm at an operating temperature of 150 C. While the CuO based sensors showed a poor response, sensitivity, and selectivity towards tested analytes. Moreover, the ZnO-NaOH based sensor revealed enormous sensitivity of 1.21 ppm-1 and a low limit of detection (LoD) of 0.018 ppm (i.e., 18 ppb) toward xylene. The ultra-sensitivity, selectivity, and low LoD of ZnO-NaOH-based sensor toward benzene and xylene are associated with the improved VO observed in the in-situ photoluminescence and electron paramagnetic resonance studies, as well as the x ray photoelectron spectroscopy analyses. The ZnO-NaOH-based sensor, which was stored for roughly 18 months (547 days), demonstrated reliable repeatability and long time operation stability for 22 hours of exposure to xylene. The superior sensitivity, stability, and selectivity indicate openly that the strategy of using various bases is a striking method for fabricating a temperature dual-mode selectivity for the detection of benzene and xylene vapours. Xylene is not just considered detrimental to the environment; it is also hazardous to humans. Herein we report on xylene vapour detection using CuO-ZnO heterostructures containing various concentrations (0.1-1.0 wt. %) of ZnO, prepared via hydrothermal synthesis. X-ray diffraction, scanning, and transmission electron microscopy, as well as x-ray photoelectron spectroscopy, validated the formation of the CuO-ZnO heterostructure. Gas detection, sensitivity, selectivity and stability tests of nine different gases, namely benzene, toluene, ethylbenzene, xylene, ethanol, methane, SO2, NO2, and CO2 at various operational temperatures were subsequently investigated. It was found that a CuO-ZnO heterostructure with 1.0 wt. % ZnO showed excellent selectivity towards 100 ppm of xylene at 100 C. The sensor further demonstrated an insignificant cross-sensitivity (Sxylene/Stoluene= 2.7) and (Sxylene/Sbenzene = 8.5) towards toluene and benzene vapour. Additionally, the ultra-low limit of detection of 9.5 ppb and sensitivity of 0.063 ppm-1 were observed towards xylene vapour, which indicated that the CuO-ZnO (1.0 wt. %) heterostructure-based sensor can produce sub-ppb-level xylene concentration. The sensor disclosed excellent long term stability in dry air and 40% relative humidity. Finally, at room temperature, the CuO-ZnO (0.5 wt. %) based sensor disclosed a superior selectivity towards NO2. Additionally, concerning other gases, the sensors showed poor responses at room temperature. While at higher temperatures, the sensors showed better selectivity towards xylene. Thus, these findings showed that while the sensors could detect xylene at high temperatures, nonetheless, the room temperature sensitivity of the CuO-ZnO (0.5 wt. %) based sensor towards NO2 denoted that the sensor could be used for low power consumption. The superior gas sensing characteristics could be ascribed to the creation of p-n heterojunction, the robust chemical affinity, and the catalytic performance of p-type CuO on xylene and NO2 gases.
Thesis (M.Sc. (Physics)) -- University of Limpopo. 2023
Keywords: Gaseous benzene; Toluene; Ethylbenzene; Xylene (BTEX); Oxides; Semiconductors; Electronic control systems; Humidity; Heterostructures